An engineered micropattern to reduce bacterial colonization, platelet adhesion and fibrin sheath formation for improved biocompatibility of central venous catheters - May, Rhea M; Magin, Chelsea M; Mann, Ethan E; Drinker, Michael C; Fraser, John C; Siedlecki, Christopher A; Brennan, Anthony B; Reddy, Shravanthi T (Clinical and translational medicine, 2015)
Background Catheter-related bloodstream infections (CRBSIs) and catheter-related thrombosis (CRT) are common complications of central venous catheters (CVC), which are used to monitor patient health and deliver medications. CVCs are subject to protein adsorption and platelet adhesion as well as colonization by the natural skin flora ( i.e. Staphylococcus aureus and Staphylococcus epidermidis ). Antimicrobial and antithrombotic drugs can prevent infections and thrombosis-related complications, but have associated resistance and safety risks. Surface topographies have shown promise in limiting platelet and bacterial adhesion, so it was hypothesized that an engineered Sharklet micropattern, inspired by shark-skin, may provide a combined approach as it has wide reaching anti-fouling capabilities. To assess the feasibility for this micropattern to improve CVC-related healthcare outcomes, bacterial colonization and platelet interactions were analyzed in vitro on a material common for vascular access devices. Methods To evaluate bacterial inhibition after simulated vascular exposure, micropatterned thermoplastic polyurethane surfaces were preconditioned with blood proteins in vitro then subjected to a bacterial challenge for 1 and 18 h. Platelet adhesion was assessed with fluorescent microscopy after incubation of the surfaces with platelet-rich plasma (PRP) supplemented with calcium. Platelet activation was further assessed by monitoring fibrin formation with fluorescent microscopy after exposure of the surfaces to platelet-rich plasma (PRP) supplemented with calcium in a flow-cell. Results are reported as percent reductions and significance is based on t -tests and ANOVA models of log reductions. All experiments were replicated at least three times. Results Blood and serum conditioned micropatterned surfaces reduced 18 h S. aureus and S. epidermidis colonization by 70% (p ≤ 0.05) and 71% (p < 0.01), respectively, when compared to preconditioned unpatterned controls. Additionally, platelet adhesion and fibrin sheath formation were reduced by 86% and 80% (p < 0.05), respectively, on the micropattern, when compared to controls. Conclusions The Sharklet micropattern, in a CVC-relevant thermoplastic polyurethane, significantly reduced bacterial colonization and relevant platelet interactions after simulated vascular exposure. These results suggest that the incorporation of the Sharklet micropattern on the surface of a CVC may inhibit the initial events that lead to CRBSI and CRT.